Efektifitas Mekanisme Bonding: Kasus Perusahaan-Perusahaan yang Dikontrol Komisaris Independen - Hadri Kusuma; Erlan Susanto (Jurnal Akuntansi dan Auditing Indonesia, 2004)
The management of the companies is expected to work at the interest of stockholders. To reduce the different interests such as agency problem between the management and stockholders, it is necessary to build an independent party that can monitor the performance of the management. This study examines the effectiveness of dividend and debt bonding for those companies listed on the JSX controlled by independent commissioners. The result of this study shows that the existence of the independent commissioners does not play important roles in minimizing the different interest (agency problem) between the two parties.Keywords: bonding, komisaris independen, hutang dan dividen